2015
DOI: 10.1002/cm.21257
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of CARMIL‐family genes during zebrafish development

Abstract: CARMILs are a conserved family of large multidomain proteins that regulate and target actin assembly by interacting with actin capping protein (CP). Vertebrates contain three highly conserved CARMIL isoforms encoded by three genes, whereas lower organisms contain only one isoform and gene. In order to investigate the functions of vertebrate CARMILs, we identified and characterized the three CARMIL genes in zebrafish (Danio rerio). We isolated and sequenced complete and partial cDNAs from embryos. The three gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…However, our study does not include an analysis of the protein products that would test this view definitively. The observation that only maternal zygotic but not zygotic carmil3 mutants presented gastrulation phenotypes, is consistent with known significant maternal carmil3 expression, which is likely to compensate for the lack of zygotic expression during gastrulation (Solnica-Krezel, 2020; Stark and Cooper, 2015). The lack of full penetrance for the later phenotypes indicates a substantial level of robustness in the processes of cell migration and morphogenesis, consistent with observations for many other genes regulating early embryogenesis (Chen et al, 2018;Kelly et al, 2000;Li-Villarreal et al, 2015;Solnica-Krezel and Driever, 2001).…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…However, our study does not include an analysis of the protein products that would test this view definitively. The observation that only maternal zygotic but not zygotic carmil3 mutants presented gastrulation phenotypes, is consistent with known significant maternal carmil3 expression, which is likely to compensate for the lack of zygotic expression during gastrulation (Solnica-Krezel, 2020; Stark and Cooper, 2015). The lack of full penetrance for the later phenotypes indicates a substantial level of robustness in the processes of cell migration and morphogenesis, consistent with observations for many other genes regulating early embryogenesis (Chen et al, 2018;Kelly et al, 2000;Li-Villarreal et al, 2015;Solnica-Krezel and Driever, 2001).…”
Section: Discussionsupporting
confidence: 79%
“…CARMILs are one family of capping-protein-interacting (CPI-motif) proteins, reviewed in (Edwards et al, 2014). Vertebrates, including zebrafish, have three conserved CARMILencoding genes, called CARMIL1, CARMIL2 and CARMIL3 in humans (Stark et al, 2017;Stark and Cooper, 2015). The zebrafish genes, carmil1, carmil2 and carmil3, have distinct spatial and temporal expression patterns during development (Stark and Cooper, 2015).…”
Section: Carmil Regulation Of Actin Assembly Via Capping Proteinmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the three, CARMIL1 is most widely expressed, being present in the skin, fins, branchial arches, gut, and cloaca (Stark and Cooper, 2015). An RNA-sequencing study of zebrafish skin found only the CARMIL1 isoform ( Wang, Cokus, and Sagasti, personal communication).…”
Section: Roles Of Carmils At the Cellular And Organismal Levelsmentioning
confidence: 99%
“…Amoebozoa and invertebrates have one gene encoding CARMIL, whereas vertebrates have three ( Liang et al , 2009 ; Edwards et al , 2014 ; Stark and Cooper, 2015 ), and the genomes of fungi and plants appear to lack CARMIL homologues altogether. The three vertebrate isoforms, CARMIL1, 2, and 3, can be defined and distinguished from each other by conserved differences in their amino acid sequences ( Figure 1 ).…”
Section: Carmil-family Proteinsmentioning
confidence: 99%